Solutions for Teachers’ Challenges in Developing Competencies in The Metaverse Era - Yuliadi, Yuliadi (Madaris: Jurnal Guru Inovatif, 2024)
Abstract Lack of motivation, unwilling asking capable colleagues, comfortable in their work position and lack of facilities have become problems for teachers in developing competencies. This research points to analyze solutions for teachers’ challenges in developing competencies in the Metaverse era. The type of this research was descriptive qualitative and purposive sampling was used to select informants. Data were collected through interview guides, observation guidelines and questionnaires. Data obtained from interviews and observations were analyzed through Miles and Huberman model. Meanwhile, data obtained from questionnaires were analyzed through descriptive analysis. Method triangulation was used to check data trustworthiness. The finding of this research reveals that teachers should improve their digital literacy skills by following training about Metaverse, pursuing education to a higher level, mastering foreign languages, reading books and research related to the Metaverse, being active in scientific forums, conducting research, and publishing articles related to Metaverse. The results of this study are expected to motivate teachers to use Metaverse in teaching.